DEEP LEARNING DAN LITERASI BUDAYA DALAM PEMBELAJARAN LAGU DAERAH: MODEL INOVATIF MELALUI KURIKULUM MERDEKA MENUJU PENDIDIKAN BERKUALITAS - Taufik Hidayat; Sintya Nurfitria Putri; Azfar, Adimas Akma Danish; Hartono; Syahrul Syah Sinaga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to formulate an integrated model for deep learning and cultural literacy in teaching regional songs at the junior high/senior high school level within the Merdeka Curriculum framework. Amidst the cultural literacy crisis and the dominance of global pop music that threatens the existence of regional songs among teenagers, a more meaningful and inclusive learning approach is needed. Using a qualitative, literature-based design, this study analyzed curriculum documents and literature on deep learning, cultural literacy, and SDG 4.7. The results show that regional songs are highly relevant to the Music Arts Learning Outcomes and the Global Diversity dimension of the Pancasila Student Profile. The developed integration model consists of four continuous stages: Contextual Exploration, Critical Appreciation, Reflection and Connection, and Creative Expression. The inclusive characteristic is the main uniqueness of this model, as the absence of demands for musical technical skills as prerequisites allows all students to actively participate. This model contributes to achieving SDG 4.7 targets by strengthening the appreciation of cultural diversity and strengthening the Global Diversity dimension in the Pancasila Student Profile. This research provides practical implications for teachers and curriculum developers in designing meaningful and inclusive regional song learning